Pathology of Marek’s disease virus-induced atherosclerosis in hypercholesterolaemic chickens - ISLAM, S; SINGH, S D; SAH, R L (The Indian Journal of Animal Sciences, 2013)
Experimental studies were carried out to elucidate the pathology and pathogenesis of MDV -induced atherosclerosis in hypercholesterolaemic chickens. In MDV infected hypercholesterolaemic chickens there were more fatty lesions as well as fatty-proliferative type of lesions compared to virus infected normocholesterolaemic chickens and the lipid accumulations were demonstrated in the aortas and brachiocephalic arteries by histochemical stainings. There appeared to be a synergy between virus infection and cholesterol dietary supplementation on the development of atherosclerotic lesions.